2022
DOI: 10.3389/fcell.2022.1035513
|View full text |Cite
|
Sign up to set email alerts
|

Understanding laterality disorders and the left-right organizer: Insights from zebrafish

Abstract: Vital internal organs display a left-right (LR) asymmetric arrangement that is established during embryonic development. Disruption of this LR asymmetry—or laterality—can result in congenital organ malformations. Situs inversus totalis (SIT) is a complete concordant reversal of internal organs that results in a low occurrence of clinical consequences. Situs ambiguous, which gives rise to Heterotaxy syndrome (HTX), is characterized by discordant development and arrangement of organs that is associated with a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 281 publications
0
14
0
Order By: Relevance
“…In zebrafish, the transgenic line Tg(sox17:EGFP) has been developed to label the DFC/KV cells (Liu et al, 2019), and several developmental steps have been identified to build a functional KV/Cilia. DFCs appear at mid-epiboly stages, migrate, proliferate, and then undergo a mesenchymal-to-epithelial transition to form KV in early somite stage (Forrest et al, 2022). KV develops directional fluid flow and establishes LR signaling, and then breaks down around 18 hpf when KV cells undergo a epithelial to mesenchymal transition (Amack, 2021) and migrate away to incorporate into muscle and notochord (Ikeda et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In zebrafish, the transgenic line Tg(sox17:EGFP) has been developed to label the DFC/KV cells (Liu et al, 2019), and several developmental steps have been identified to build a functional KV/Cilia. DFCs appear at mid-epiboly stages, migrate, proliferate, and then undergo a mesenchymal-to-epithelial transition to form KV in early somite stage (Forrest et al, 2022). KV develops directional fluid flow and establishes LR signaling, and then breaks down around 18 hpf when KV cells undergo a epithelial to mesenchymal transition (Amack, 2021) and migrate away to incorporate into muscle and notochord (Ikeda et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Establishment of left-right patterning (LR Patterning) is an important event in early embryonic development, organ asymmetry defect is closely related to the occurrence of various congenital diseases such as congenital heart disease and schizophrenia (Gabriel and Lo, 2020; Huang et al, 2014). Although the mechanisms of establishment of organ LR patterning are complex and diverse in different animal models (Hamada and Tam, 2020; Onuma et al, 2020; Zhu et al, 2020), the role of Kupffer’s vesicle (KV)/Node-Cilia axis in zebrafish and mice is extremely conservative (Forrest et al, 2022; Grimes and Burdine, 2017; Little and Norris, 2021). In zebrafish, the normal development of KV precursor cells (Named dorsal forerunner cells (DFCs) and KV morphogenesis/Ciliogenesis play crucial roles in initiating left-sided signals in the embryonic lateral plate mesoderm (LPM) (Grimes and Burdine, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The system was classi ed into two categories: the presence of a tooth (0) and the absence of speci c tooth types, each assigned a distinct value. Central incisor (1), lateral incisor (2), canine (4), rst premolar (8), second premolar (16), rst molar (32), second molar (64), and third molar (128) were each associated with their respective values. The cumulative score was derived from the sum of these values corresponding to the missing tooth types in each quadrant, yielding a unique numeric representation for each pattern of tooth agenesis.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that some molecules, acting as the left-right organizers, controlling laterality, may be both involved during palatogenesis and odontogenesis (32). Some genes involved in left-right patterning contribute to facial asymmetry of the CLP spectrum (33).…”
Section: Supernumerary Teethmentioning
confidence: 99%
“…Their developmental origins and the mechanisms determining their rotation direction are unclear. Both genetics and physical constraints could be implicated in determining the location and orientation of whorls, as in other lateralisation phenomena (Forrest et al 2022). As is Blaschko lines, which include whorl-like distributions on the scalp surface (Happle 2013), hair whorls may be related with cell migration processes but there is no current experimental evidence for this hypothesis.…”
mentioning
confidence: 99%